Data underpinning "Seasonal and Temporal Changes during Storage Affect Quality Attributes of Green Asparagus" - Anastasiadi, Maria; Collings, Emma R.; Terry, Leon A.; Shivembe, Allan; Qian, Binghua (Cranfield University, 2019)
This dataset contains the data used for statistical analysis and predictive modelling in the paper entitled "Seasonal and Temporal Changes during Storage Affect Quality Attributes of Green Asparagus". Specifically it contains physiological and biochemical changes in asparagus spears from two different cultivars during shelf-life captured over the course of the harvest season, as well as during cold storage and subsequent shelf-life for three different cultivars. Physiological changes include moisture loss, respiration rate, cutting energy, stiffness, objective colour. Biochemical data include individual sugars, ascorbic acid and abscisic acid and its catabolites. Also the data capture spatial differences along the asparagus spears (apical and basal regions).
Keywords: sugars'; 'storage'; 'cultivar'; 'abscisic acid (ABA)'; 'Crop and Pasture Post Harvest Technologies (incl. Transportation and Storage)'